Nature of extrinsic and intrinsic self-trapping of charge carriers in underdoped cuprate high-Tc superconductors - Ganiev, O.K. (Condensed Matter Physics, 2016)
Nature of extrinsic and intrinsic self-trapping (ST) of charge carriers in cuprates have been studied theoretically.
The binding energies and radii of the extrinsic and intrinsic large polarons and bipolarons in cuprates are calculated variationally using the continuum model and adiabatic approximation. We have shown that the extrinsic
and intrinsic three-dimensional (3D) large bipolarons exist in underdoped cuprates at η = ε∞/ε₀ < 0.127 and
η < 0.138, respectively [where ε∞(ε₀) is the optic (static) dielectric constant]. Теоретично вивчено природу зовнiшнiх i внутрiшнiх самозахопних носiїв струму в купратах. Енергiї
зв’язування i радiуси зовнiшнiх i внутрiшнiх великих поляронiв i бiполяронiв в купратах обчислено
варiацiйно, використовуючи неперервну модель та адiабатичне наближення. Ми показали, що зовнiшнi i внутрiшнi тривимiрнi великi бiполярони iснують в слабозлегованих купратах, вiдповiдно, при
η = ε∞/ε₀ < 0.127 i η < 0.138 [де ε∞(ε₀) — оптична (статична) дiелектрична стала].